Analysis of Vehicle-Bridge Coupling Vibration Characteristics of Curved Girder Bridges - Hengtao Cao; Yao Lu; Daihai Chen (Applied Sciences, 2024)
When vehicles move on a bridge, the coupling effect between vehicles and bridges can affect driving safety and comfort, especially for curved bridges, therefore, choosing reasonable design parameters for curved bridges is crucial. In this article, a three-span curved continuous box-girder bridge was taken as the research object; the entire process of vehicle-bridge coupling vibration of highway curved girder bridges was conducted via numerical simulation and the vehicle-bridge coupling vibration analysis program Cmck 1.0 was developed. Then, the influence factors such as curvature radius, constraint mode, and vehicle characteristics on the vehicle-bridge coupling vibration of curved girder bridges were explored. The results showed that as the curvature radius increased, the dynamic response of the bridge offered a gradually decreasing trend and compared to the vertical dynamic response, the torsional response was more sensitive to the influence of the curvature radius. Different constraint methods significantly impacted the dynamic response of bridges, and the vertical and torsional dynamic responses of bridges under general constraint arrangement of straight bridges were increased compared to those under boundary conditions for curved beam bridges. As the axle load of the car decreases, the bridge mid-span vertical and torsional dynamic responses showed a decreasing trend. In contrast, the lateral dynamic response gradually increased.